Homo Oeconomicus as the Homo Moralis' Party Pooper: Heterogeneous Morality in Public Good Games - Thomas Eichner; Marco Runkel (CESifo GmbH, 2024)
The main insight of this paper is that moral behavior does not necessarily alleviate coordination problems or may even worsen them, if individuals possess different degrees of morality. We characterize heterogenous Alger-Weibull morality preferences in a canonical model of voluntary contributions to a public good. The analysis reveals a novel polarization effect which traces back to a 'preference for leadership' and weakens (strengthens) the incentive to contribute to the public good for individuals with below (above) average morality. Equilibrium public good provision is not increased by morality, as long as there are homo oeconomicus individuals. An increase in morality of an individual may reduce total provision of the public good, if heterogeneity is large enough. Redistributive transfers are no longer neutral.
Keywords: C72; D91; H41; 330; moral behaviour; Kantian ethics; heterogeneity; public goods